Discretionary Disclosure: A Note. - Richardson, Scott (Abacus, 2001)
This article extends the models of discretionary disclosure. The level of disclosure will be affected by the costs of such disclosure. Verrecchia (1983) shows that when the cost of disclosure is fixed then the threshold level of disclosure is positively related to that cost. Verrecchia (1990a) shows that in the presence of fixed disclosure costs the threshold level of disclosure is negatively related to the quality of information (precision) to be disclosed. The intuition for the result is that as information is more precise, withholding it is more detrimental for the firm and hence the threshold for disclosure is lowered. The model here expands the cost of disclosure to be a function of information quality. When this is the case, the Verrecchia (1990a) unambiguous result does not hold. The presence of information quality in the cost function creates a countervailing force such that more precise information does not necessarily imply more disclosure. This creates the intuitive result that precise information of a proprietary nature might be withheld from the market.